Analisis Dampak Implementasi BYOND by BSI terhadap Risiko Operasional dan Risiko Reputasi: Studi Kasus Bank Syariah Indonesia - Chauzaqi, Farah (Maliki Interdisciplinary Journal, 2025)
Islamic banking is increasingly developing with digitalization, one of which is through BYOND by BSI which is designed to improve service efficiency. However, the implementation of this application faces operational challenges that have an impact on the reputation of Bank Syariah Indonesia (BSI). System disruptions due to maintenance, digital infrastructure failures, and cybersecurity threats such as alleged hacking have triggered customer dissatisfaction and increased reputational risk. This study uses a qualitative approach with a case study method, based on literature analysis and secondary data. The results show that weaknesses in operational risk management can increase reputational risk, especially in the banking industry that relies on public trust. To address this, BSI needs to improve system security, improve user experience, and ensure transparency in communication with customers. With more proactive mitigation measures and effective risk management strategies, BSI can strengthen operational stability and maintain customer trust in its digital banking services.